Corrections to a recently published area taxonomy of Australia - Ebach, Malte C.; Gill, Anthony C.; Kwan, Alan; Ahyong, Shane T.; Murphy, Daniel J.; Cassis, Gerasimos (Zootaxa, 2013)
After the publication of “Towards an Australian Bioregionalisation Atlas: A provisional area taxonomy of Australia’s biogeographical regions” (Ebach et al. 2013), we were informed of an incorrect, and missing type locality for the Cape York Peninsula respectively. The correct type locality for the Cape York Peninsula Cracraft 1991 phyto- and zoogeographical sub-regions, is McIlwraith Range, Coen, Queensland, Australia, 13°46'27.00"S 143°19'18.00"E.